Fair haven [videorecording (DVD)] - Malloy, Tom, 1974-; Taylor, Jennifer, 1972 April 19-; Wopat, Tom; Grant, Michael; Harrison, Gregory, 1950- (2015)
After a long stay in ex-gay conversion therapy, James, a young piano prodigy, returns home to his family farm and his emotionally distant father, Richard. After Richard pressures James to give up on his music career and take over the farm, James agrees as a way to make up for his past. Soon, however, James finds himself face to face with a former lover, Charlie, who wants to help him turn away from his new beliefs and family expectations, and follow his dreams of studying music.